Multiple primary lung cancer: Updates of clinical management and genomic features - Tian, He; Bai, Guangyu; Yang, Zhenlin; Chen, Ping; Xu, Jiachen; Liu, Tiejun; Fan, Tao; Wang, Bingning; Xiao, Chu; Li, Chunxiang; Gao, Shugeng; He, Jie (Frontiers in Oncology, 2023)
In recent decades, multiple primary lung cancer (MPLC) has been increasingly prevalent in clinical practice. However, many details about MPLC have not been completely settled, such as understanding the driving force, clinical management, pathological mechanisms, and genomic architectures of this disease. From the perspective of diagnosis and treatment, distinguishing MPLC from lung cancer intrapulmonary metastasis (IPM) has been a clinical hotpot for years. Besides, compared to patients with single lung lesion, the treatment for MPLC patients is more individualized, and non-operative therapies, such as ablation and stereotactic ablative radiotherapy (SABR), are prevailing. The emergence of next-generation sequencing has fueled a wave of research about the molecular features of MPLC and advanced the NCCN guidelines. In this review, we generalized the latest updates on MPLC from definition, etiology and epidemiology, clinical management, and genomic updates. We summarized the different perspectives and aimed to offer novel insights into the management of MPLC. Keywords Multiple primary lung cancer (MPLC), Clinical Management, Genomic, Heterogeneity, Intrapulmonary Metastasis (IPM).